Aqueous synthesis of Z-scheme photocatalyst powders and thin-film photoanodes from earth abundant elements - Šutka, Andris; Vanags, Martins; Joost, Urmas; Smits, Krisjanis; Ruža, Jurģis; Locs, Janis; Kleperis, Janis; Juhna, Talis (Elsevier Ltd, 2018)
Solid-state narrow band gap semiconductor heterostructures with a Z-scheme charge-transfer mechanism are the most promising photocatalytic systems for water splitting and environmental remediation under visible light. Herein, we construct all-solid Z-scheme photocatalytic systems from earth abundant elements (Ca and Fe) using an aqueous synthesis procedure. A novel Z-scheme two-component Fe2O3/Ca2Fe2O5 heterostructure is obtained in a straightforward manner by soaking various iron-containing nanoparticles (amorphous and crystalline) with Ca(NO3)2 and performing short (20min) thermal treatments at 820°C. The obtained powder materials show high photocatalytic performances for methylene blue dye degradation under visible light (45 mW/cm2), exhibiting a rate constant up to 0.015min-1. The heterostructure exhibits a five-fold higher activity compared to that of pristine hematite. The experiments show that amorphous iron-containing substrate nanoparticles trigger the Fe2O3/Ca2Fe2O5 heterostructure formation. We extended our study to produce Fe2O3/Ca2Fe2O5 nanoheterostructure photoanodes via the electrochemical deposition of amorphous iron-containing sediment were used. The visible-light (15mW/cm2) photocurrent increases from 183μA/cm2 to 306μA/cm2 after coupling hematite and Ca2Fe2O5. Notably, the powders and photoanodes exhibit distinct charge-transfer mechanisms evidenced by the different stabilities of the heterostructures under different working conditions.
Riga Technical University supported the preparation of this manuscript from the Scientific Research Project Competition for Young Researchers No. ZP 2017/8
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Hematite; Photoanode; Photocatalyst; Photoelectrochemical properties; Z-scheme